Autophagy-lysosomal signaling responses to heat stress in tenotomy-induced rat skeletal muscle atrophy - Muthita Hirunsai (2022)
Aims: The autophagy-lysosomal system plays a crucial role in maintaining muscle proteostasis. Excessive stimulation of the autophagic machinery is a major contributor to muscle atrophy induced by tendon transection. Hyperthermia is known to attenuate muscle protein loss during disuse conditions; however, little is known regarding the response of the autophagy pathway to heat stress following tenotomy-induced muscle atrophy. The purpose of this study was to evaluate whether heat stress would have a beneficial impact on the activation of autophagy in tenotomized soleus and plantaris muscles. Main methods: Male Wistar rats were divided into control, control plus heat stress, tenotomy, and tenotomy plus heat stress groups. The effects of tenotomy were evaluated at 8 and 14 days with heat treatment applied using thermal blankets (30 min. day−1, at 40.5–41.5 °C, for 7 days). Key findings: Heat stress could normalize tenotomy-induced muscle loss and over-activation of autophagy-lysosomal signaling; this effect was evidently observed in soleus muscle tenotomized for 14 days. The autophagy-related proteins LC3B-II and LC3B-II/I tended to decrease, and lysosomal cathepsin L protein expression was significantly suppressed. While p62/SQSTM1 was not altered in response to intermittent heat exposure in tenotomized soleus muscle at day 14. Phosphorylation of the 4E-BP1 protein was significantly increased in tenotomized plantaris muscle; whereas heat stress had no impact on phosphorylation of Akt and FoxO3a proteins in both tenotomized muscles examined. Significance: Our results provide evidence that heat stress associated attenuation of tenotomy-induced muscle atrophy is mediated through limiting over-activation of the autophagy-lysosomal pathway in oxidative and glycolytic muscles.